Conductivity of the PGT Synthesized by the High Energy Ball Milling (HEBM) - S. K. S. Parashar; M. Ghoranneviss; A. Salar Elahi (Advances in Materials Science and Engineering)
Nanocrystalline Pb1−3x/2GdxTiO3 (where x=0.01) abbreviated as PGT has been synthesised by high energy ball milling at room temperature. Milling was continuous and X-ray analysis shows that single phase tetragonal structure of nanocrystalline PGT was formed after 15 h milling. The average crystallite size was found to be 17 nm. The frequency dependent ac conductivity of the PGT ceramic was studied in the range 100–525°C. Complex impedance analysis suggested the dielectric relaxation to be of non-Debye type. The activation energy was found to be 1.04 ev. The mechanism of charge transport in nanocrystalline PGT was successfully explained by correlated hopping model.